THE COMPATIBILITY OF AUTONOMOUS WEAPONS WITH THE PRINCIPLE OF DISTINCTION IN THE LAW OF ARMED CONFLICT. Issue 4 (October 2020) - Winter, Elliot
Abstract: The law of armed conflict requires 'distinction' between civilians and combatants and provides that only the latter may be targeted. However, for proper implementation, distinction requires advanced observation and recognition abilities as well as the capacity to exercise judgement based on situational awareness. While the observation and recognition abilities of machines may now surpass those of humans, the capacity of machines to exercise judgement remains significantly more limited than our own. Consequently, this article contends that the deployment of 'autonomous weapons' based on current levels of technological sophistication would be incompatible with distinction and that, as such, their use in conflict would be unlawful.